Muskmelons - Marr, Charles W.; Tisserat, Ned; Bauernfeind, Robert; Gast, Karen L. B. (My University, 1998)
This publication is for commercial vegetable production, specifically the production of muskmelons in Kansas.
MF1109_1998_10
Keywords: MF1109; Crops; Fruits and Vegetables; Equipment and Structures; MF